Synthesis of acyl-hydrazone from usnic acid and isoniazid and its anti-Mycobacterium tuberculosis activity (2017)
Compound usnic acid (1), isolated from lichen Evernia prunastri (Cajamarca-Peru) and the synthesis and characterization of its acyl-hydrazone (2), from the condensation reaction between usnic acid and isoniazid in an ethanol solution under reflux, giving an overall yield of 95%, were evaluated. Both compounds were evaluated and compared with isoniazid according to its anti-Mycobacterium tuberculosis activity based on the tetrazolium microplate assay (TEMA). Compound 1 had MIC (minimal inhibitory concentration) value of 16.0 μg/mL in each test of H37Rv (susceptible type), TB DM 97 (resistant wild type) and MDR DM 1098 (multi drug resistances type) strains. In similar tests, compound 2 MIC values were 2.0, 64.0 and 64.0 μg/mL respectively.